What are Thai SME companies motivations for export and how they have chosen their international market which consequently influences on their performance? - Theywin, Katirat (2006)
The purpose of this study is to explore global motivations and the international market selection behaviour of Thai SME exporting companies. The effect of international market selection behaviour on export performance is also investigated. The study is accomplished by the application of two research methods, namely questionnaire and the semi-structured interview with exporting firms. This paper is divided into 5 chapters. First chapter describes the research issues and the objectives of the study. Chapter 2 reviews some traditional frameworks explaining the global motivations of firm, potential determinants of the firms choice of foreign market and international market selection approaches. Research methodology and data collection are contained in chapter 3 while chapter 4 illustrates results of the study and discussion. The final chapter draws up conclusions and implications for companies and for future researches. The study found that most of Thai SME companies are more likely to pursue proactive motivations for export than reactive motivations. Profit motive is considered as the most important driving force for firms which proactively engage in export. It appears that SME firms pay more attention to external/environmental factors than internal factors when deciding their foreign markets. Firms are greatly influenced by economic growth, competitive environment, market size and political stability respectively. Finally, the findings of this study clearly establish that international market selection behaviour has no apparent influence on export performance of SME companies. There is no significant difference between the performance levels of companies adopting opportunistic behaviour and systematic behaviour in terms of profit growth, turnover and market share.